Polyolefin composition, polyolefin microporous membrane and lithium battery

By adopting polyolefin composition and adjusting its molecular weight distribution, the problem of the reduction in strength of the wet polyolefin base film after thinning is solved, and a high-strength and high-breathability polyolefin microporous film is realized, which is suitable for high-end lithium battery separators.

CN119798858AActive Publication Date: 2025-04-11TSINGHUA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510286386.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The existing wet polyolefin base film has a problem of lowering strength after further thinning, resulting in a decrease in the safety of the diaphragm.

Method used

A polyolefin composition is adopted, including a first polyolefin with a number average molecular weight of 200w to 220w, a second polyolefin with a number average molecular weight of 140w to 160w, and a third polyolefin with a number average molecular weight of 40w to 60w. By adjusting its mass proportion and adding mineral oil and antioxidants, the unwrap of the ultra-high molecular weight polyolefin is promoted and the mechanical properties and breathability of the microporous membrane are improved.

Benefits of technology

The processing based on high molecular weight polyolefin-based film has been achieved. The obtained polyolefin microporous film has obvious advantages in terms of mechanical properties and breathability. The puncture strength is 60-90 g/μm and the bidirectional tensile strength is 250-350 MPa, which is suitable for high-end lithium battery separators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a polyolefin composition, a polyolefin microporous membrane and a lithium battery, the polyolefin composition comprises first polyolefin with a number-average molecular weight of 200w-220w, second polyolefin with a number-average molecular weight of 140w-160w and third polyolefin with a number-average molecular weight of 40w-60w, and the usage amount of the polyolefin composition satisfies the following formula: (B-C) / A is more than or equal to 1 and less than or equal to 3.5; wherein A represents the mass ratio of the first polyolefin, B represents the mass ratio of the second polyolefin, and C represents the mass ratio of the third polyolefin; according to the invention, the second polyolefin with high molecular weight and the third polyolefin with low molecular weight are introduced into the first polyolefin with ultra-high molecular weight, and unwrapping of long-chain molecules of the polyolefin with ultra-high molecular weight is promoted by utilizing the co-plasticizing effect of the second polyolefin with low molecular weight and the third polyolefin with small molecular mineral oil; and the processing of the high molecular weight polyolefin-based membrane is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of diaphragms and preparation methods, and in particular to a polyolefin composition, a polyolefin microporous membrane and a lithium battery. Background Art

[0002] The diaphragm is one of the core materials of lithium batteries. With the continuous increase in sales of new energy vehicles at home and abroad, the safety of its core component - lithium batteries has become a top priority for the development of the industry. The diaphragm is an important link in improving the high temperature resistance of lithium batteries, inhibiting thermal failure, and optimizing the safety factor. Its thinness, low cost, high heat resistance, high membrane rupture temperature and other indicators determine the energy density, cycle life, safety and other performance of downstream lithium battery products. With the rapid development of the domestic power battery industry, low-end and medium-end diaphragms have basically been localized, but in the field of high-end diaphragms, there are still many technical, process and equipment barriers. There is still a large gap in the thinness and physical and chemical performance indicators of diaphragm products. my country's high-end diaphragms have long relied on imports. With the continuous increase in the demand for high safety and high energy in the lithium battery industry, the requirements for high heat resistance and thinness of diaphragms are also continuously increasing. Therefore, it is of great significance to develop new ultra-thin and high-heat-resistant coatings to enhance the comprehensive performance of diaphragms and thus improve the safety of batteries.

[0003] Ultra-thin base film, high porosity and high mechanical strength are the mainstream directions of market demand. Wet-process polyolefin (PE) base film has more advantages than dry-process diaphragm in terms of thinness, mechanical properties, and air permeability. However, after further thinning, the wet-process polyolefin base film has the problem of reduced strength and reduced safety of the diaphragm. The mechanical strength of the diaphragm depends to a large extent on the molecular weight of the polyolefin used in the base film processing. Ultra-high molecular weight polyolefin has become the preferred main material for ultra-thin and high-strength polyolefin base film due to its advantages such as low density, high strength and high modulus. However, the long chain molecules of high molecular weight polyolefin are highly entangled, the melt viscosity is high, and the flow rate is low, which leads to difficult processing and poor film forming. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a polyolefin composition, a polyolefin microporous membrane and a lithium battery. The lithium battery separator prepared by the polyolefin composition has excellent mechanical properties and air permeability. The specific invention content is as follows: In a first aspect, the present invention provides a polyolefin composition comprising: The first polyolefin with a number average molecular weight of 200w to 220w, the second polyolefin with a number average molecular weight of 140w to 160w, and the third polyolefin with a number average molecular weight of 40w to 60w, the amounts thereof satisfy the following formula: 1≤(BC) / A≤3.5; Wherein, A represents the mass proportion of the first polyolefin, B represents the mass proportion of the second polyolefin, and C represents the mass proportion of the third polyolefin.

[0005] Optionally, the mass proportion of the first polyolefin is 1-6%, the mass proportion of the second polyolefin is 45-55%, and the mass proportion of the third polyolefin is 40-48%.

[0006] Optionally, the first polyolefin is selected from polyethylene and / or polypropylene; the second polyolefin is selected from polyethylene and / or polypropylene; and the third polyolefin is selected from polyethylene and / or polypropylene.

[0007] Optionally, the polyolefin composition further comprises mineral oil.

[0008] Optionally, the mass ratio of the total mass of the first polyolefin, the second polyolefin and the third polyolefin to the mineral oil is (15-30):(75-82).

[0009] Optionally, the mineral oil is selected from one or more combinations of white oil, petroleum ether, petroleum hydrocarbons and paraffin oil.

[0010] Optionally, the polyolefin composition further comprises an antioxidant.

[0011] Optionally, the mass ratio of the total mass of the first polyolefin, the second polyolefin and the third polyolefin to the antioxidant is (15-30): (0.1-0.5).

[0012] Optionally, the antioxidant is selected from one or more combinations of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and N,N-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionamide].

[0013] In a second aspect, the present invention provides a polyolefin microporous membrane, comprising the polyolefin composition described in the first aspect.

[0014] Optionally, the polyolefin microporous membrane is obtained by the following preparation method: The first polyolefin with a number average molecular weight of 200w-220w, the second polyolefin with a number average molecular weight of 140w-160w, the third polyolefin with a number average molecular weight of 40w-60w, mineral oil and an antioxidant are melt-blended to form an oil film by casting the obtained mixed melt; The oil film is subjected to biaxial stretching to form a film, and then subjected to extraction treatment and heat setting treatment to obtain the polyolefin microporous membrane.

[0015] Optionally, in the mixed melt, the mass ratio of the total mass of the first polyolefin, the second polyolefin and the third polyolefin to the mass of the mineral oil and the antioxidant is (15-30): (75-82): (0.1-0.5).

[0016] Optionally, the mass of the first polyolefin accounts for 1-6% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin; The mass of the second polyolefin accounts for 45-55% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin; The mass of the third polyolefin accounts for 40-48% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin.

[0017] Optionally, the temperature of the mixed melt is 150-250°C.

[0018] Optionally, the extractant used in the extraction treatment process is selected from a combination of one or more of n-hexane, n-heptane, dichloromethane, chloroform, isopropanol and ethanol.

[0019] Optionally, the polyolefin microporous membrane has a thickness of 5 to 10 μm.

[0020] Optionally, the puncture strength of the polyolefin microporous membrane is 60 to 90 g / μm.

[0021] Optionally, the biaxial tensile strength of the polyolefin microporous membrane is 250-350 MPa.

[0022] In a third aspect, the present invention provides a lithium battery comprising the polyolefin microporous membrane described in the second aspect.

[0023] Compared with the prior art, the present invention has the following advantages: The present invention provides a polyolefin composition for preparing a polyolefin microporous membrane, comprising: a first polyolefin with a number average molecular weight of 200w to 220w, a second polyolefin with a number average molecular weight of 140w to 160w, and a third polyolefin with a number average molecular weight of 40w to 60w, and the amounts thereof satisfy the following formula: 1≤(BC) / A≤3.5; wherein A represents the mass proportion of the first polyolefin, B represents the mass proportion of the second polyolefin, and C represents the mass proportion of the third polyolefin.

[0024] In the preparation method provided by the present invention, according to the disentanglement process of high molecular weight polyolefin molecules and the variation law of the melt index of the composite melt, a high molecular weight second polyolefin (number average molecular weight of 1.4 million to 1.6 million) and a low molecular weight third polyolefin (number average molecular weight of 400,000 to 600,000) are introduced into an ultra-high molecular weight first polyolefin (number average molecular weight of 2 million to 2.2 million), and the co-plasticizing effect of them and small molecular weight mineral oil is utilized to promote the disentanglement of ultra-high molecular weight polyolefin long chain molecules; the processing of a base film based on a high molecular weight polyolefin (formulated molecular weight of more than 1 million) is realized, and compared with existing commercial diaphragms, the polyolefin microporous membrane prepared by the polyolefin composition provided by the present invention has obvious advantages in various performance parameters, especially the ability to take into account both air permeability and mechanical properties. The obtained polyolefin microporous membrane has a thickness of 5 to 10 μm, an air permeability of 190 to 230 s / 100 cc, a diaphragm puncture strength of 60 to 90 g / μm, and a diaphragm biaxial tensile strength of 250 to 350 MPa. DETAILED DESCRIPTION

[0025] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the prior art can be used. The reagents and other instruments used without specifying the manufacturer are all conventional reagent products that can be purchased commercially.

[0026] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.

[0027] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0028] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0029] In a first aspect, the present invention provides a polyolefin composition comprising: The first polyolefin with a number average molecular weight of 200w to 220w, the second polyolefin with a number average molecular weight of 140w to 160w, and the third polyolefin with a number average molecular weight of 40w to 60w, the amounts thereof satisfy the following formula: 1≤(BC) / A≤3.5; Wherein, A represents the mass proportion of the first polyolefin, B represents the mass proportion of the second polyolefin, and C represents the mass proportion of the third polyolefin.

[0030] In specific implementation, due to the high entanglement of ultra-high molecular weight polyolefin long-chain molecules, high melt viscosity, and low flow rate, there are problems of poor film-forming properties and high processing difficulty during the film-forming process; therefore, the embodiment of the present invention selects an ultra-high molecular weight first polyolefin (number average molecular weight of 2 million to 2.2 million), a high molecular weight second polyolefin (number average molecular weight of 1.4 million to 1.6 million), and a low molecular weight third polyolefin (number average molecular weight of 400,000 to 600,000) to form a polyolefin composition, and its dosage satisfies the following formula: 1≤(BC) / A≤3.5; wherein A represents the mass proportion of the first polyolefin, B represents the mass proportion of the second polyolefin, and C represents the mass proportion of the third polyolefin; this makes the polyolefin composition have a wider molecular weight distribution, which helps to optimize the performance of the microporous membrane. At the same time, the co-plasticization effect between them and mineral oil is used to promote the disentanglement of ultra-high molecular weight polyolefin long-chain molecules; and the processing of high molecular weight polyolefin (formulated molecular weight of more than 1 million) base film is realized.

[0031] In specific implementation, the present invention regulates the mass proportion of an ultra-high molecular weight first polyolefin (number average molecular weight of 2 million to 2.2 million), a high molecular weight second polyolefin (number average molecular weight of 1.4 million to 1.6 million), and a low molecular weight third polyolefin (number average molecular weight of 400,000 to 600,000) in a polyolefin composition based on performance requirements such as tensile strength, puncture strength, and air permeability; wherein the ultra-high molecular weight polyolefin has extremely high mechanical strength, which can improve the tensile strength and tear resistance of the microporous membrane; the high molecular weight polyolefin has good flexibility, which can enable the microporous membrane to withstand bending and deformation; the low molecular weight polyolefin can reduce the melt viscosity and adjust the pore size and porosity of the microporous membrane.

[0032] Furthermore, the mass proportion of the first polyolefin is 1-6%, the mass proportion of the second polyolefin is 45-55%, and the mass proportion of the third polyolefin is 40-48%; after a large number of experimental investigations, the present invention found that the mass proportions of the first polyolefin, the second polyolefin, and the third polyolefin satisfy 1≤(BC) / A≤3.5 (A represents the mass percentage of the first polyolefin, B represents the mass percentage of the second polyolefin, and C represents the mass percentage of the third polyolefin), so that the obtained polyolefin microporous membrane can take into account both air permeability and mechanical properties. The obtained polyolefin microporous membrane has a membrane thickness of 5-10μm, a membrane puncture strength of 60-90 g / μm, and a membrane biaxial tensile strength of 250-350 MPa; when the mass proportion of the first polyolefin in the polyolefin microporous membrane does not satisfy the above-mentioned mass relationship formula, the membrane cannot be dissolved and processed, the membrane puncture strength is low, the tensile strength is low, etc., and the actual application cannot be met; compared with existing commercial membranes, the polyolefin microporous membrane developed by the present invention has obvious advantages in various performance parameters.

[0033] In some embodiments, the first polyolefin may be selected from polyethylene or polypropylene; the second polyolefin may be selected from polyethylene or polypropylene; and the third polyolefin may be selected from polyethylene or polypropylene.

[0034] In some embodiments, the polyolefin composition further includes mineral oil, and the mass ratio of the total mass of the first polyolefin, the second polyolefin, and the third polyolefin to the mineral oil is controlled at (15-30): (75-82). The addition of mineral oil can effectively adjust the phase separation process of the polyolefin composition when preparing the diaphragm material using the thermally induced phase separation (TIPS) process, which is beneficial to control the porosity and pore size distribution of the diaphragm. In addition, since the number average molecular weight of the first polyolefin is relatively large, this will cause high melt viscosity during processing and increase the difficulty of processing. The present invention utilizes the co-plasticizing effect between small molecule mineral oil and the first polyolefin, the second polyolefin, and the third polyolefin to promote the disentanglement of ultra-high molecular weight polyolefin long chain molecules; realizes the processing based on high molecular weight polyolefin base film; in addition, the addition of mineral oil can also significantly reduce the melt viscosity, help the uniform dispersion of polyolefin molecular chains, improve fluidity, and facilitate extrusion, stretching and other process operations; In some embodiments, the mineral oil may be selected from a combination of one or more of white oil, petroleum ether, petroleum hydrocarbons and paraffin oil.

[0035] In some embodiments, the polyolefin composition further includes an antioxidant, and the total mass of the first polyolefin, the second polyolefin, and the third polyolefin is controlled at a mass ratio of (15-30): (0.1-0.5); the addition of the antioxidant can increase the temperature of high-temperature thermal decomposition of the polyolefin, and effectively prevent the polymer from thermal oxidation degradation during high-temperature processing of the polyolefin composition, resulting in molecular chain breakage, crosslinking or discoloration. The antioxidant can interrupt the chain reaction and maintain the material properties by capturing free radicals (such as RO·, ROO·). In addition, the addition of the antioxidant can also prevent the oxidation of polyolefins to generate chromophores (such as carbonyl groups), keeping the appearance of the diaphragm transparent.

[0036] In some embodiments, the antioxidant is selected from one or more combinations of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and N,N-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionamide].

[0037] In a second aspect, the present invention provides a polyolefin microporous membrane comprising the polyolefin composition described in the first aspect.

[0038] In specific implementation, the polyolefin microporous membrane is obtained by the following preparation method: The first polyolefin with a number average molecular weight of 200w-220w, the second polyolefin with a number average molecular weight of 140w-160w, the third polyolefin with a number average molecular weight of 40w-60w, mineral oil and an antioxidant are melt-blended to form an oil film by casting the obtained mixed melt; The oil film is subjected to biaxial stretching to form a film, and then subjected to extraction treatment and heat setting treatment to obtain the polyolefin microporous membrane.

[0039] In a specific implementation, the mineral oil is selected from a combination of one or more of white oil, petroleum ether, petroleum hydrocarbon and paraffin oil. The antioxidant is selected from a combination of one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and N,N-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionamide].

[0040] In a specific implementation, the present invention mixes the first polyolefin, the second polyolefin, the third polyolefin, the mineral oil and the antioxidant in a mass ratio of (15-30): (75-82): (0.1-0.5) according to the total mass of the first polyolefin, the second polyolefin and the third polyolefin, and the mineral oil and the antioxidant. Then, the mixture is added into a twin-screw extruder for plasticization and blending to form a mixed melt at 150-250°C. The obtained mixed melt is then cooled on a chilled roller in a casting manner to form an oil film, and then the oil film is biaxially stretched, and then the mineral oil therein is extracted and removed using an extractant, and finally heat-set to obtain a polyolefin microporous membrane.

[0041] Based on the performance requirements of tensile strength, puncture strength, air permeability and the like, the present invention combines an ultra-high molecular weight first polyolefin (number average molecular weight of 2 million to 2.2 million), a high molecular weight second polyolefin (number average molecular weight of 1.4 million to 1.6 million), and a low molecular weight third polyolefin (number average molecular weight of 400,000 to 600,000) to prepare a polyolefin microporous membrane; wherein the mass of the first polyolefin accounts for 1 to 6% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin; the mass of the second polyolefin accounts for 45 to 55% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin; and the mass of the third polyolefin accounts for 40 to 48% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin. The obtained polyolefin microporous membrane can achieve both air permeability and mechanical properties. The membrane thickness of the obtained polyolefin microporous membrane is 5-10 μm, the membrane puncture strength is 60-90 g / μm, and the membrane biaxial tensile strength is 250-350 MPa. Compared with existing commercial membranes, the polyolefin microporous membrane developed by the present invention has obvious advantages in various performance parameters.

[0042] In some embodiments, the extractant used in the extraction process is selected from a combination of one or more of n-hexane, n-heptane, dichloromethane, chloroform, isopropanol and ethanol.

[0043] In a third aspect, the present invention provides a lithium battery comprising the polyolefin microporous membrane described in the second aspect.

[0044] In order to enable those skilled in the art to more clearly understand the present invention, a polyolefin composition, a polyolefin microporous membrane and a lithium battery according to the present invention are now described in detail through the following examples.

[0045] Embodiment 1: The polyolefin composition, mineral oil and antioxidant are uniformly mixed in a mass ratio of 17.5:82:0.5; added into a twin-screw extruder for plasticization and blending to form a mixed melt at 220°C; The mixed melt formed by the twin-screw extruder is cast through a die head and a chill roller to form an oil film, the oil film is biaxially stretched, the mineral oil therein is extracted and removed by an extractant, and finally the polyolefin microporous membrane is obtained by heat setting; The mass percentage of the polyolefin composition used is as follows: the mass percentage of the first polyolefin (number average molecular weight of 200w-220w) is A 5%, the mass percentage of the second polyolefin (number average molecular weight of 140w-160w) is B 50%, and the mass percentage of the third polyolefin (number average molecular weight of 40w-60w) is C 45%; the first polyolefin, the second polyolefin and the third polyolefin used are all polypropylene; the mineral oil used is paraffin oil; the antioxidant used is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate isooctyl alcohol ester. The extractant used is n-heptane. The mass percentage relationship of the polyolefin composition is (BC) / A=1, which meets the requirement of 1≤(BC) / A≤3.5.

[0046] The performance test results are shown in Table 1.

[0047] Embodiment 2: The polyolefin composition, mineral oil and antioxidant are uniformly mixed in a mass ratio of 24.9:75:0.1; added into a twin-screw extruder for plasticization and blending to form a mixed melt at 150°C; The mixed melt formed by the twin-screw extruder is cast through a die head and a chill roller to form an oil film, the oil film is biaxially stretched, the mineral oil therein is extracted and removed by an extractant, and finally the polyolefin microporous membrane is obtained by heat setting; The mass percentage of the polyolefin composition used is as follows: the mass percentage of the first polyolefin (number average molecular weight of 200w-220w) is A 1%, the mass percentage of the second polyolefin (number average molecular weight of 140w-160w) is B 51%, and the mass percentage of the third polyolefin (number average molecular weight of 40w-60w) is C 48%; the first polyolefin, the second polyolefin and the third polyolefin used are all polyethylene; the mineral oil used is petroleum hydrocarbon; the antioxidant used is N,N-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionamide]; and the extractant used is dichloromethane. Among them, the mass percentage relationship of the polyolefin composition is (BC) / A=3, which meets the requirement of 1≤(BC) / A≤3.5.

[0048] The performance test results are shown in Table 1.

[0049] Embodiment 3: The polyolefin composition, mineral oil and antioxidant are uniformly mixed in a mass ratio of 19.6:80:0.4; added into a twin-screw extruder for plasticization and blending to form a mixed melt at 180°C; The mixed melt formed by the twin-screw extruder is cast through a die head and a chill roller to form an oil film, the oil film is biaxially stretched, the mineral oil therein is extracted and removed by an extractant, and finally the polyolefin microporous membrane is obtained by heat setting; The mass percentage of the polyolefin composition used is as follows: the mass percentage of the first polyolefin (number average molecular weight of 200w-220w) is A 4%, the mass percentage of the second polyolefin (number average molecular weight of 140w-160w) is B 55%, and the mass percentage of the third polyolefin (number average molecular weight of 40w-60w) is C 41%; the first polyolefin, the second polyolefin and the third polyolefin used are all polypropylene; the mineral oil used is white oil; the antioxidant used is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid n-octadecyl ester; the extractant used is n-hexane. Among them, the mass percentage relationship of the polyolefin composition is (BC) / A=3.5, which meets the requirement of 1≤(BC) / A≤3.5.

[0050] The performance test results are shown in Table 1.

[0051] Embodiment 4: The polyolefin composition, mineral oil and antioxidant are uniformly mixed in a mass ratio of 21.7:78:0.3; added into a twin-screw extruder for plasticization and blending to form a mixed melt at 230°C; The mixed melt formed by the twin-screw extruder is cast through a die head and a chill roller to form an oil film, the oil film is biaxially stretched, the mineral oil therein is extracted and removed by an extractant, and finally the polyolefin microporous membrane is obtained by heat setting; The mass percentage of the polyolefin composition used is as follows: the mass percentage of the first polyolefin (number average molecular weight of 200w-220w) is A 6%, the mass percentage of the second polyolefin (number average molecular weight of 140w-160w) is B 54%, and the mass percentage of the third polyolefin (number average molecular weight of 40w-60w) is C 40%; the first polyolefin, the second polyolefin and the third polyolefin used are all polyethylene; the mineral oil used is paraffin oil; the antioxidant used is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate isooctyl ester; the extractant used is n-hexane. Among them, the mass percentage relationship of the polyolefin composition is (BC) / A=2.33, which meets the requirement of 1≤(BC) / A≤3.5.

[0052] The performance test results are shown in Table 1.

[0053] Embodiment 5: The polyolefin composition, mineral oil and antioxidant are uniformly mixed in a mass ratio of 19.8:80:0.2; added into a twin-screw extruder for plasticization and blending to form a mixed melt at 250°C; The mixed melt formed by the twin-screw extruder is cast through a die head and a chill roller to form an oil film, the oil film is biaxially stretched, the mineral oil therein is extracted and removed by an extractant, and finally the polyolefin microporous membrane is obtained by heat setting; The mass percentage of the polyolefin composition used is as follows: the mass percentage of the first polyolefin (number average molecular weight of 200w-220w) is A 3%, the mass percentage of the second polyolefin (number average molecular weight of 140w-160w) is B 50%, and the mass percentage of the third polyolefin (number average molecular weight of 40w-60w) is C 47%; the first polyolefin, the second polyolefin and the third polyolefin used are all polypropylene; the mineral oil used is petroleum ether; the antioxidant used is N,N-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionamide]; and the extractant used is dichloromethane. Among them, the mass percentage relationship of the polyolefin composition is (BC) / A=1, which meets the requirement of 1≤(BC) / A≤3.5.

[0054] The performance test results are shown in Table 1.

[0055] Comparative Example 1: Compared with Example 1, the polyolefin composition does not contain the first polyolefin, but only contains the second polyolefin and the third polyolefin, and the mass ratio of the second polyolefin to the third polyolefin is 50:45. Others are the same as in Example 1.

[0056] Comparative Example 2: The mass percentage of the polyolefin composition used is as follows: the mass percentage A of the first polyolefin (number average molecular weight of 200w-220w) is 10%, the mass percentage B of the second polyolefin (number average molecular weight of 140w-160w) is 40%, and the mass percentage C of the third polyolefin (number average molecular weight of 40w-60w) is 50% (wherein the mass percentage relationship of the polyolefin composition is (BC) / A=-1, which does not satisfy the formula 1≤(BC) / A≤3.5); the rest is consistent with Example 1.

[0057] Comparative Example 3: The existing commercial lithium-ion battery separator is composed of polyethylene with a number average molecular weight of 100~120w; model SW809I, the manufacturer is Shenzhen Xingyuan Material Technology Co., Ltd.

[0058] Table 1 Test results of polyolefin microporous membrane properties

[0059] It can be seen from the performance test results shown in Examples 1-5 that the polyolefin microporous membrane provided by the present invention has a membrane thickness of 5-10 μm, and in the polyolefin composition, the mass proportion of the first polyolefin is 1-6%, the mass proportion of the second polyolefin is 45-55%, and the mass proportion of the third polyolefin is 40-48%, and the surface density is 4.5-5.3 g / m 2 The air permeability is 190-230 s / 100cc, the diaphragm puncture strength is 60-90 g / μm, and the diaphragm biaxial tensile strength is 250-350 MPa.

[0060] By comparing the performance test results of Example 1 with those of Comparative Example 1, it can be seen that since Comparative Example 1 shows that there is no first polyolefin in the polyolefin composition constituting the polyolefin microporous membrane, the puncture strength and tensile strength of the polyolefin microporous membrane provided by Comparative Example 1 are both lower than those of the polyolefin microporous membrane provided by Example 1.

[0061] By comparing the performance test results of Example 1 and Comparative Example 2, since the mass ratio of the first polyolefin (A), the second polyolefin (B) and the third polyolefin (C) in the polyolefin microporous membrane given in Comparative Example 2 does not satisfy the relationship of 1≤(BC) / A≤3.5, its mechanical properties are worse than those of the polyolefin microporous membrane provided in Example 1.

[0062] In addition, by comparing the performance test results of Example 1 and Comparative Example 3, it is found that the polyolefin microporous membrane obtained by the preparation method provided by the present invention can take into account the advantages of both air permeability and mechanical properties, while the commercial diaphragm is significantly inferior in mechanical properties.

[0063] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0064] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.

[0065] The above is a detailed introduction to a polyolefin composition, a polyolefin microporous membrane and a lithium battery provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A polyolefin composition, characterized in that include: The first polyolefin with a number average molecular weight of 200w to 220w, the second polyolefin with a number average molecular weight of 140w to 160w, and the third polyolefin with a number average molecular weight of 40w to 60w, the amounts thereof satisfy the following formula: 1≤(BC) / A≤3.5; Wherein, A represents the mass proportion of the first polyolefin, B represents the mass proportion of the second polyolefin, and C represents the mass proportion of the third polyolefin.

2. The polyolefin composition according to claim 1, characterized in that The mass proportion of the first polyolefin is 1-6 %, the mass proportion of the second polyolefin is 45-55 %, and the mass proportion of the third polyolefin is 40-48 %.

3. The polyolefin composition according to claim 1, characterized in that The first polyolefin is selected from polyethylene and / or polypropylene; the second polyolefin is selected from polyethylene and / or polypropylene; and the third polyolefin is selected from polyethylene and / or polypropylene.

4. The polyolefin composition according to claim 1, characterized in that The polyolefin composition also includes mineral oil.

5. The polyolefin composition according to claim 4, characterized in that The mass ratio of the total mass of the first polyolefin, the second polyolefin and the third polyolefin to the mass of the mineral oil is (15-30):(75-82).

6. The polyolefin composition according to claim 4, characterized in that The mineral oil is selected from one or more combinations of white oil, petroleum ether, petroleum hydrocarbon and paraffin oil.

7. The polyolefin composition according to claim 1, characterized in that The polyolefin composition also includes an antioxidant.

8. The polyolefin composition according to claim 7, characterized in that The mass ratio of the total mass of the first polyolefin, the second polyolefin and the third polyolefin to the mass of the antioxidant is (15-30):(0.1-0.5).

9. The polyolefin composition according to claim 7, characterized in that The antioxidant is selected from one or more combinations of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and N,N-1,6-hexylene-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionamide].

10. A polyolefin microporous membrane, characterized in that: The polyolefin composition comprises the polyolefin composition described in any one of claims 1 to 9.

11. The polyolefin microporous membrane according to claim 10, characterized in that: The polyolefin microporous membrane is obtained by the following preparation method: The first polyolefin with a number average molecular weight of 200w-220w, the second polyolefin with a number average molecular weight of 140w-160w, the third polyolefin with a number average molecular weight of 40w-60w, mineral oil and an antioxidant are melt-blended to form an oil film by casting the obtained mixed melt; The oil film is subjected to biaxial stretching to form a film, and then subjected to extraction treatment and heat setting treatment to obtain the polyolefin microporous membrane.

12. The polyolefin microporous membrane according to claim 11, characterized in that: In the mixed melt, the mass ratio of the total mass of the first polyolefin, the second polyolefin and the third polyolefin to the mass of the mineral oil and the antioxidant is (15-30): (75-82): (0.1-0.5).

13. The polyolefin microporous membrane according to claim 11, characterized in that: The mass of the first polyolefin accounts for 1 to 6% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin; The mass of the second polyolefin accounts for 45-55% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin; The mass of the third polyolefin accounts for 40-48% of the total mass of the first polyolefin, the second polyolefin and the third polyolefin.

14. The polyolefin microporous membrane according to claim 11, characterized in that: The temperature of the mixed melt is 150-250°C.

15. The polyolefin microporous membrane according to claim 11, characterized in that: The extractant used in the extraction treatment process is selected from one or more combinations of n-hexane, n-heptane, dichloromethane, chloroform, isopropanol and ethanol.

16. The polyolefin microporous membrane according to claim 10, characterized in that: The thickness of the polyolefin microporous membrane is 5-10 μm.

17. The polyolefin microporous membrane according to claim 10, characterized in that: The puncture strength of the polyolefin microporous membrane is 60 to 90 g / μm.

18. The polyolefin microporous membrane according to claim 10, characterized in that: The biaxial tensile strength of the polyolefin microporous membrane is 250-350 MPa.

19. A lithium battery, characterized in that: The invention comprises the polyolefin microporous membrane according to any one of claims 10 to 18.

Citation Information

Patent Citations

  • High-elongation polyolefin diaphragm and application thereof

    CN110931688A

  • Polyolefin diaphragm as well as preparation method and application thereof

    CN115458867A

  • Polymer composition blends and films made therefrom

    CN118922993A

  • Porous membranes and polymer blend made therewith

    WO2025039154A1